China–Japan interaction in the Middle East: a battleground of Japan's remilitarization. Issue 2 (4th March 2017) - Evron, Yoram
ABSTRACT: As most studies on Middle East–East Asian relations focus on the interregional dimension, the manner in which relations between East Asian powers influence, and are influenced by, their policies in the Middle East are largely overlooked. Attempting to add another layer to the study of Sino-Japanese relations, this article explores whether Sino-Japanese rivalry extends to the Middle East. This undertaking requires a conceptual distinction between measures related to Sino-Japanese competition in the Middle East and measures which are related to their rivalry. Building on a minimal definition of interstate rivalry, the article argues that neither the effort to secure energy supply nor their economic or political competition there is shaped by their rivalry. The only field that can be associated with that rivalry is Japan's quasi-military activity in the Middle East, which may enhance its security policy's revision. That, in turn, causes much concern and criticism in Beijing, thus assigning the region a certain role in their relations.